Relationship of Self-Care Based on Orem Theory to the Risk of Peripheral Neuropathy in Diabetic Patients Type 2 Mellitus at the Tilongkabila Health Center - Nanda Ariesta Aprilia Abas; Ita Sulistiani; Erwin Purwanto (Universitas Muhammadiyah Palu, 2026)
This study aims to find out how the relationship between self-care and the risk of peripheral neuropathy in patients with type 2 diabetes mellitus at the Tilongkabila Health Center. This type of research is quantitative using a correlational design, which aims to find out whether there is a relationship between two or more variables with the approach used, namely cross-sectional. Based on the results of the study, obtained from 74 respondents, it shows that most of the respondents have good self-care, namely 50 respondents (67.6%), followed by respondents with sufficient self-care as many as 11 respondents (14.9%), and less self-care as many as 13 respondents (17.6%). The results of neuropathy screening examination using monofilament found that as many as 41 respondents (55.4%) were not at risk of developing peripheral neuropathy, while 33 respondents (44.6%) were at risk of peripheral neuropathy. There was a statistically significant relationship between self-care based on Orem's theory and the risk of peripheral neuropathy in patients with type 2 diabetes mellitus at the Tilongkabila Health Center, with a p-value of 0.043 (p < 0.05).